A new definition of the genus Petrocodon (Gesneriaceae) - Weber, A.; Wei, Y. G.; Puglisi, C.; Wen, F.; Mayer, V.; Moller, M. (Phytotaxa, 2011)
Based on molecular studies, the small Chinese genus Petrocodon (two species and one variety) has been recently enlarged to include the monotypic genera Calcareoboea, Paralagarosolen and Tengia. It is shown here that the (6-7) species of Lagarosolen, the monotypic Dolicholoma, a few species of Didymocarpus, and a number of new species that have recently been published (but not formally described) under Petrocodon and Lagarosolen should be included in this genus. This raises the size of the genus from five to around 20 species. With respect to the floral diversity (corolla form, size, and coloration; with the exception of Tengia, the androecium is always diandrous) and inferred pollination syndromes (different forms of melittophily, ornithophily, psycho- and/or sphingophily), Petrocodon represents one of the most varied genera of Old World Gesneriaceae, comparable to some New World genera.